2023
DOI: 10.1038/s41561-023-01254-8
|View full text |Cite
|
Sign up to set email alerts
|

Arctic warming by abundant fine sea salt aerosols from blowing snow

Xianda Gong,
Jiaoshi Zhang,
Betty Croft
et al.

Abstract: The Arctic warms nearly four times faster than the global average, and aerosols play an increasingly important role in Arctic climate change. In the Arctic, sea salt is a major aerosol component in terms of mass concentration during winter and spring. However, the mechanisms of sea salt aerosol production remain unclear. Sea salt aerosols are typically thought to be relatively large in size but low in number concentration, implying that their influence on cloud condensation nuclei population and cloud properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…This mechanism could account for the small particles seen during Antarctic winter at coastal stations (Giordano et al, 2018;Frey et al, 2020). Recently, similar PNSD were reported by Gong et al, (2023) in the central 515…”
Section: Possible Primary Sourcessupporting
confidence: 76%
See 1 more Smart Citation
“…This mechanism could account for the small particles seen during Antarctic winter at coastal stations (Giordano et al, 2018;Frey et al, 2020). Recently, similar PNSD were reported by Gong et al, (2023) in the central 515…”
Section: Possible Primary Sourcessupporting
confidence: 76%
“…Arctic over an entire year from September 2019 to October 2020 during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition, showing that blowing snow was observed more than 20% of the time from November to April. The sublimation of blowing snow generates high concentrations of fine-mode sea salt aerosol (diameter below 300 nm), enhancing 520 cloud condensation nuclei concentrations up to tenfold above background levels (Gong et al, 2023).…”
Section: Possible Primary Sourcesmentioning
confidence: 99%
“…and underestimates AOD along the Canadian archipelago region by -9.3%. This difference may arise from the model inadequately addressing natural aerosol formation due to increased open ocean emissions from sea ice loss, as suggested in prior studies (Breider et al, 2017;Schmale et al, 2021;Gong et al, 2023). It is also possible new particle formation over the high Arctic ice pack occurs.…”
Section: J F M a M J Jmentioning
confidence: 98%
“…In particular, the model representations of the effects and development of clouds (Pithan et al, 2014;Kretzschmar et al, 2020;Stevens and Kluft, 2023), and of the interactions of the atmosphere with sea ice, snow on sea ice, and ocean physics as well as biogeochemical feedback processes are challenging (Rinke et al, 2019;Huang et al, 2019;Pefanis et al, 2020). In addition, the role of aerosol particles in Arctic amplification has not been sufficiently investigated (Schmale et al, 2021;Dada et al, 2022;Gong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%